Testing altruistic behavior using an online experiment. - Nigini Oliveira (10284854) (2025)
(a) The screenshot shows both players, one in a blue chef’s cap on the left side (Chef 1) and the other in a green one on the right side (Chef 2), in front of their respective stoves (dark gray with a black bar inside). The goal is to cook and deliver as many onion soups as possible within a given time limit by putting three onions (yellow ovals with stalks) on the stove, picking up an empty bowl (white circle), collecting the cooked soup in the bowl from the stove, and delivering the bowl to customers (light grey location). Players have separate scores and can choose to cook soups individually (to get points) or share onions. Players can share onions by placing them on the “cooperation bridge” (square colored green between the two kitchens). Note that as depicted in (a), the path for the player on the left (blue cap) to get to the (continually replenished) store of onions (at the bottom of the kitchen) is much shorter compared to the path for the player on the right (green cap). Each study participant plays Round 1 (altruistic behavior baseline) on the left side, Round 2 (altruistic/non-altruistic bot demonstration round) on the right side, and Round 3 (behavior change examination round) on the left side again. When the computer-controlled bot is playing on the left in Round 2, it randomly selects one of two possible behaviors: altruistic behavior, where the bot places onions on the cooperation bridge for the human player, or non-altruistic behavior, where the bot does not help and focuses on maximizing its own score. (b) In this screenshot, the players are in front of their onion stores. The exclamation icon on the cooperation bridge denotes a call for help issued by the player on the right before going all the way to the southeast end to get onions from their own store.